Improving Basic Teaching Skill Quality through Peer Teaching Simulation which Based on Experiential Learning - Yani Supriani; Tatang Herman; Turmudi Turmudi; Rina Oktaviyanthi; Ria Novia Agus (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to improve the basic skills of teaching fiveth semester students of the Mathematic Education study program Serang Raya University 2020/2021 academic year through the application of peer teaching simulation based on Eksperiential Learning technique. The subjects in this study were the fiveth semester students of the Mathematic Education Study Program 2020/2021 academic year totaling 31 people. The data in this study were collected by tests and the results were analyzed quantitatively supported by qualitative interpretations. The results show that the application of peer teaching simulation with Eksperiential Learning technique can improve the basic teaching skills of the sixth semester students of the Mathematic Education Study Program Serang Raya University 2020/2021 academic year from the percentage of success in the first cycle of 87,10% to 93,55% in cycle to 74, 97 in the second cycle. Therefore, the application of peer teaching simulation with eksperiential learning technique is recommended to be used in lectures that target the formation of skills or competencies of prospective teachers.